2010
DOI: 10.1093/nar/gkq237
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of mRNA abundance in two life-cycle stages of Trypanosoma brucei and identification of splicing and polyadenylation sites

Abstract: Transcription of protein-coding genes in trypanosomes is polycistronic and gene expression is primarily regulated by post-transcriptional mechanisms. Sequence motifs in the untranslated regions regulate mRNA trans-splicing and RNA stability, yet where UTRs begin and end is known for very few genes. We used high-throughput RNA-sequencing to determine the genome-wide steady-state mRNA levels (‘transcriptomes’) for ∼90% of the genome in two stages of the Trypanosoma brucei life cycle cultured in vitro. Almost 6% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
328
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(350 citation statements)
references
References 49 publications
21
328
1
Order By: Relevance
“…5B). These minor poly(A) sites were also reported in previous studies using RNA-Seq technology [42,43].…”
Section: Mapping Gpeet Mrna 3 Ends Reveals Transcript Deadenylation Asupporting
confidence: 82%
See 1 more Smart Citation
“…5B). These minor poly(A) sites were also reported in previous studies using RNA-Seq technology [42,43].…”
Section: Mapping Gpeet Mrna 3 Ends Reveals Transcript Deadenylation Asupporting
confidence: 82%
“…Furthermore, the most frequent oligo(U) tail was enriched in late PF cultures 6 h after addition of ActD. Why did transcriptomewide analyses previously performed in T. brucei [42,43] not identify the uridylyl tails? One possibility is that the mapping algorithms employed resulted in annotation of the sequences as non-assignable reads and might have been ignored.…”
Section: Discussionmentioning
confidence: 99%
“…While no sequence consensus for polyadenylation or SL addition have been found in trypanosomatids, several studies have demonstrated that polypyrimidine-rich regions within intergenic regions guide SL addition and the polyadenylation of upstream and downstream genes, respectively, resulting in the generation of mature mRNAs (Hartmann et al 1998, López-Estraño et al 1998. The sequence requirements for T. cruzi, T. brucei and Leishmania mRNA processing were initially investigated by comparing expressed sequence tags and/or cDNAs with genomic sequences (Benz et al 2005, Campos et al 2008, Smith et al 2008 and, more recently, they have been investigated using deep sequencing RNA (Kolev et al 2010, Nilsson et al 2010, Siegel et al 2010. Campos et al (2008) reported the average distance from the polypyrimidine tract to the SL addition site and to the polyadenylation site as well as the median lengths of the 5' and 3' untranslated regions (UTR) in T. cruzi genes.…”
mentioning
confidence: 99%
“…34 Since alternative polyadenylation is common in trypanosomes as well, CFIm25 identified here is a potential regulator of this process. 35,36 In other eukaryotes, a direct linkage between spliceosomal and 3 0 end processing components had been demonstrated by several studies. [37][38][39] In trypanosomes, so far only the polypyrimidine tract is known to affect trans splicing and polyadenylation of two adjacent genes.…”
Section: Discussionmentioning
confidence: 93%